Different Concepts of Health Tourism in Europe and The Meaning of Health Tourism Worldwide - Marica Mazurek, (International Journal of Advanced Science and Technology, 2020)
Health tourism (which part is also spa tourism and wellness) in Europe has a long-term tradition. The concept of health tourism is very different in European and in North American culture as well as in Asian culture. The article will provide a framework for the distinction of different concepts of health tourism in specific countries of Europe and compare the approaches, specifically in Slovakia, Portugal and Nordic countries (Finland) in comparison to the North American concept (Canada) and Asian perception (Taiwan, Malaysia, etc.). Selected cases might be a good example for the explanation of different approaches to health tourism in Europe. Methods applied in the exploratory and empirically based study were used in the framework of the secondary research. There have been used specific cases – only the examples from different parts of the world. This study acknowledges the merits of qualitative research as it provides a pragmatic response for an in-depth understanding for this exploratory research.